Operating performance Pumping in Central Pivot using Inverter Frequency - Lima, Adenilsom dos Santos; Zocoler, Joao Luiz [UNESP]; Jadoski, Sidnei Osmar; Maggi, Marcio Furlan; Amarante, Regiane Rodrigues do (Univ Estadual Centro-oeste, 2015)
The study aimed to evaluate the variation of the following parameters: rotation of the motor pump set, power developed by the electric motor and reduction of energy consumption in pumping set of the center pivot irrigation system, operating in two programming levels the frequency inverter and three positions of operation. The experimental design was completely randomized, being made three replications in each tested position. It was applied to analysis of variance Followed by Tukey's test. Two operation conditions were tested: Test 1 with constant pressure in the output of motor pump set, and Test 2 with variable rotation in accordance with the need of pressure of system. For each condition of operation were tested three positions of lines of collecting: incline of 3.45%, level and slope with 11.78%. The results showed that the lateral line position significantly influenced the rotation of the motor pump set, consequently, the power developed by the engine and the power consumption. Mainly in the test 2 condition, showing the frequency inverter operating mode.
Keywords: Rotation; consumption; power; irrigation